2012
DOI: 10.1038/bjc.2012.253
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating benign from malignant solid breast masses: value of shear wave elastography according to lesion stiffness combined with greyscale ultrasound according to BI-RADS classification

Abstract: Background:The aim of this study was to assess the performance of shear wave elastography combined with BI-RADS classification of greyscale ultrasound images for benign/malignant differentiation in a large group of patients.Methods:One hundred and seventy-five consecutive patients with solid breast masses on routine ultrasonography undergoing percutaneous biopsy had the greyscale findings classified according to the American College of Radiology BI-RADS. The mean elasticity values from four shear wave images w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
137
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(150 citation statements)
references
References 13 publications
6
137
2
1
Order By: Relevance
“…Berg et al recommended the use of a cut-off threshold for the maximum elasticity, E max of 80 kPa for the optimal benign/malignant differentiation [2]. Evans et al recommend a cut-off threshold for the mean elasticity, E mean of 50 kPa [4].…”
mentioning
confidence: 99%
“…Berg et al recommended the use of a cut-off threshold for the maximum elasticity, E max of 80 kPa for the optimal benign/malignant differentiation [2]. Evans et al recommend a cut-off threshold for the mean elasticity, E mean of 50 kPa [4].…”
mentioning
confidence: 99%
“…A cut-off value for mean elasticity of the ROI of 50 kPa was used for benign/malignant differentiation, as this level has been validated in previous studies. 2,6,15 Static greyscale images underwent retrospective standard BI-RADS classification by a breast radiologist and a breast radiology trainee, both blinded to the elastography and pathology findings but aware of the patient's age (Category 3: probably benign, Category 4a: low suspicion, Category 4b: intermediate suspicion, Category 4c: moderate suspicion and Category 5: highly suggestive of malignancy). 16 BI-RADS Categories 1-3 were taken as negative, since the American College of Radiology guidelines state that such lesions can be managed without immediate biopsy.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] Several large studies have shown that the addition of SWE to greyscale ultrasound improves the performance of ultrasound in differentiating benign from malignant breast masses. 1,3,6 Notably, the combination of benign SWE and greyscale ultrasound findings has been shown to be highly specific, and malignancy is extremely unlikely, with a negative-predictive value for the combination of 100%. 6 The SWE parameter of mean stiffness is highly accurate in differentiating between benign and malignant solid breast masses and has performance parameters at least as good as the Breast Imaging Reporting and Data System (BI-RADS) evaluation of greyscale images.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations